Impact of Syrian Crisis on Jordanian Economy (Global Journal of Human-Social Science, 2023)
Recent political conditions represented by the Syrian refugee crisis in Jordan depended on a reality that constitutes another challenge in achieving national stability in addition to various challenges that Jordan suffers from and its attempt to adapt to all variables and different requirements whether stemming from the internal or external environment and drawing logical policies with the aim of creating Solutions in achieving the Jordanian future based on the constants and foundations of the political system and the humanitarian aspect